Proceedings of the 2016 6th International Conference on Advanced Design and Manufacturing Engineering (ICADME 2016) 2016
DOI: 10.2991/icadme-16.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Early stage hydration properties of calcium aluminosilicate slag

Abstract: ABSTRACT:The calcium aluminosilicate slag cement clinker was prepared from bauxite-coal composite pellets by high temperature reduction and smelting process. The hydration results show that, after hydration for 28 days, the hydration products of calcium aluminosilicate slag are mainly composed of killalaite (Ca3.2(H0.6Si2O7)(OH)), calcium silicate hydrate (Ca1.5SiO3.5 · xH2O) and calcium aluminates hydroxid (3CaO·Al2O3·Ca(OH)2·18·H2O, Ca12Al13.86Fe0.14(OH)2). With the increase of w(CaO)/w(SiO2) ratio, the kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They found that the optimized process conditions were bauxite/anthracite/ slaked lime weight ratio of 100:16.17:59.37, reduction temperature at 1450°C and reduction time of 20 min. Under these conditions, high-quality iron nuggets and calcium aluminate slag were obtained and shown in Figure 7 In addition, Zhang et al [32] found that the autogenously pulverizable slag (calcium aluminate slag) cement clinker has a higher reactivity during the early stage of the hydration process, and the cement clinker of autogenously pulverizable slag is shown in Figure 8. After hydration for 28 days, the hydration products of autogenously pulverizable slag are mainly composed of killalaite (Ca 3.2 (H 0.6 Si 2 O 7 ) (OH)), calcium silicate hydrate (Ca 1.5 SiO 3.5 ÁxH 2 O) and calcium aluminates hydroxide (3CaOÁAl 2 O 3 ÁCa(OH) 2 Á18ÁH 2 O, Ca1 2 Al 13.86 Fe 0.14 (OH) 2 ).…”
Section: Comprehensive Utilization Processes Of Iron-rich Bauxitementioning
confidence: 94%
“…They found that the optimized process conditions were bauxite/anthracite/ slaked lime weight ratio of 100:16.17:59.37, reduction temperature at 1450°C and reduction time of 20 min. Under these conditions, high-quality iron nuggets and calcium aluminate slag were obtained and shown in Figure 7 In addition, Zhang et al [32] found that the autogenously pulverizable slag (calcium aluminate slag) cement clinker has a higher reactivity during the early stage of the hydration process, and the cement clinker of autogenously pulverizable slag is shown in Figure 8. After hydration for 28 days, the hydration products of autogenously pulverizable slag are mainly composed of killalaite (Ca 3.2 (H 0.6 Si 2 O 7 ) (OH)), calcium silicate hydrate (Ca 1.5 SiO 3.5 ÁxH 2 O) and calcium aluminates hydroxide (3CaOÁAl 2 O 3 ÁCa(OH) 2 Á18ÁH 2 O, Ca1 2 Al 13.86 Fe 0.14 (OH) 2 ).…”
Section: Comprehensive Utilization Processes Of Iron-rich Bauxitementioning
confidence: 94%